Середньовічне християнське паломництво і дві знахідки з Ходосівки - Готун, І.А.; Казимір, О.М.; Гунь, М.О.; Сухонос, А.М. (Археологія, 2018)
Робота присвячена зафіксованим джерелами фактам вшанування давньоруськими паломниками православних святинь Палестини та зібраним у процесі археологічних досліджень матеріальним свідченням середньовічного прочанства як соціокультурного явища. Аналізується контекст побутування перламутрового хрестика і західноєвропейського металевого паломницького нашивного хреста із зображенням Розп’яття Volto Santo, виявлених на селищі Ходосівка-Рославське. The Christianity provided not only adherence to certain canons in everyday life and the performance of rituals, but also the worship of religious relics which included the places related to the earthly life of the Savior. Sources reflect the visits to the Near Eastern religious centres of the members of each estate. The material evidence of these peregrinations are the encolpions and mother-of-pearl crosses. The workshop having produced these religious insignia was discovered in the crusader castle Atlit near Haifa and the objects were found in the Avtunychi and Hodosivka-Roslavske settlements. The crosses with sub-rectangular cross-section armstapering to the edge, with relief thickenings at the ends and depicting an oblique crossin the cross centre are dominated. Also the flat crosses, crosses with short wide arms, the “Latin” and leaf bearing ones, which are the further development of the original form, occurred. The items different from made in Atlit ones, as well as the find from Hodosivka could be produced in unknown site which is indicated by the material — the shell from the northern rivers. Thus it is premature to consider all finds as the pilgrimage relics. Apart from the mother-of-pearl cross the patched metal cross with the Crucifix Volto Santo (Holy Face) peculiar to West European pilgrimage was discovered in Khodosivka. The parallel for it, together with a pearl cross comes from the Turaida castle on the Baltic coast. Perhaps they reflect the possible visit to Palestine of the a Livonian who could worshiped the crucifixion of Volto Santo. As to the find from Khodosivka, it is more complicated: the northern origin of the pearl cross does not allow supposing the possibility of journey to Palestine of the owner of a cross around the Mediterranean Sea, and the ways and reasons of the coming of these relics to the site are still unclear. Христианство предусматривало не только следование определенным канонам и исполнение определенных обрядов, но и поклонение религиозным святыням, к которым относились и места, связанные с земной жизнью Спасителя. Источники отражают посещение религиозных центров Ближнего Востока лицами практически всех сословий, а материальным свидетельством странствий жителей Руси выступают энколпионы и перламутровые крестики. Мастерская по производству этих религиозных инсигний исследована в замке крестоносцев Атлит вблизи Хайфы, а сами вещи на селищах юга Руси выявлены в Автуничах и Ходосовке-Рославском. Преобладают кресты с сужающимися к краю, подпрямоугольными в сечении лучами, рельефно отделенными утолщениями на концах и изображением косого креста в средокрестии. Встречаются также плоские; с короткими широкими лучами; «латинские», процветшие, представляющие дальнейшее развитие начальной формы. Предметы, отличающиеся от атлитских, как и находка из Ходосовки, могли производиться в неизвестных пунктах, на что указывает изготовление последней из моллюска, распространенного в северных реках, поэтому отнесение всех находок к реликвиям паломников в Святую землю кажется преждевременным. Помимо перламутрового креста, в Ходосовке обнаружен свойственный западноевропейскому пилигримажу нашивной металлический с Распятием Volto Santo (Святой Лик). Аналогия ему вместе с крестиком из перламутра происходит из Латвии и может отражать посещения Палестины ливонцем, поклонившимся распятию Volto Santo. С ходосовской находкой сложнее: северное происхождение крестика из перламутра не позволяет рассматривать путешествие жителя селища в Палестину вокруг Средиземного моря, поэтому пути и причины попадания реликвий на памятник остаются невыясненными.